TANGGUNG JAWAB NEGARA DALAM MASA PANDEMI COVID-19 - Fradhana Putra Disantara (STIH Putri Maharaja, 2020)
The Coronavirus Disease 2019 (COVID-19) pandemic encourages the government to take various strategic steps to accelerate the handling of COVID-19. One of the strategic policies undertaken by the government is the implementation of Large-Scale Social Restrictions in various cities or districts in Indonesia. However, this abnormal policy does not mean abandoning government responsibility for all lines of community life. This legal research is aimed at analyzing the state's responsibilities in the COVID-19 pandemic and also providing formulations related to future law (ius constituendum) on the state of emergency national law. This legal research uses the statute approach and conceptual approach. Primary and secondary legal materials used in this legal research are inventoried in order to obtain proper studies and provide critical study of the legal issues discussed. The results of the study stated that state responsibility during the COVID-19 pandemic had been legitimized by existing national and international legal provisions. The Large-Scale Social Restrictions Policy (PSBB) should not derogate the principle rights of the community. For this reason, the responsibility of the state must be optimized because the community has a central position in a country. Then, a new formulation is needed as an umbrella act in the regulation of national emergency status. This is because existing laws are not relevant to current conditions.